Hydrodynamics of Compound Droplet Flowing in the Curved Minichannel - Meimei Sun; Miao Zhao; Wei Gao (Advances in Condensed Matter Physics)
Based on the volume of fluid (VOF) method, a theoretical model of compound droplet deformation in curved minichannel is developed. The effects of curved angle, continuous phase, radius ratio between the inner and integral droplets, and viscosity of the middle phase are examined to reveal the underlying mechanism of compound droplet deformation. The results indicate that the deformation process of the compound droplets in the curved minichannel can be divided into three stages, namely, the initial stage, the turning stage, and the adjustment stage. Both large curved angle and high capillary number of the continuous phase result in the large shear force and high eccentricity of the compound droplet. However, as the radius ratio increases, the influence of the inner droplet on the deformation of the compound droplet transits from enhancing to suppressing.